2021
DOI: 10.1016/j.annonc.2021.10.167
|View full text |Cite
|
Sign up to set email alerts
|

148P A phase II study of tislelizumab plus chemotherapy in EGFR mutated advanced non-squamous NSCLC patients failed to EGFR TKI therapies: First analysis

Abstract: throat and hypopharyngeal function retention rate was 84.6% (11/13). The pCR rate was 44.4% (12/27), and the major pathological response rate was 74.1% (20/27). The overall pathological downstaging rate was 100% (27/27). As of August 1, 2021, the median follow-up time was 10.5 months, and the median disease-free survival was not reached. Neoadjuvant therapy-related adverse events were all grade 1 or 2, except for a grade 3 rash reported in one patient. Regarding the surgical complications, 3 (11.1%) had intrao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The median PFS and OS were 7.0 and 23.5 months, respectively, in that study, which were superior to historical data of traditional chemotherapy (21). Tislelizumab combined with chemotherapy has been reported to achieve an overall ORR of 59.4% and DCR of 90.6% in a phase II trial (22). Compared with the results of previous studies on single-agent ICIs, these data from prospective clinical trials suggest that combination therapy may significantly improve prognosis despite a lack of direct comparison.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The median PFS and OS were 7.0 and 23.5 months, respectively, in that study, which were superior to historical data of traditional chemotherapy (21). Tislelizumab combined with chemotherapy has been reported to achieve an overall ORR of 59.4% and DCR of 90.6% in a phase II trial (22). Compared with the results of previous studies on single-agent ICIs, these data from prospective clinical trials suggest that combination therapy may significantly improve prognosis despite a lack of direct comparison.…”
Section: Discussionmentioning
confidence: 59%
“…With the further understanding of the synergistic mechanism of chemotherapy and immunotherapy, as well as the release of data from the clinical trial Impower150, more studies are focusing on the efficacy of immunotherapy-based combination treatment in EGFR-mutated NSCLC after EGFR-TKI resistance. In phase II trials, toripalimab and tislelizumab were reported to have objective response rates (ORRs) of 50.0% and 59.4% and disease control rates (DCRs) of 87.5% and 90.6%, respectively, in combination with chemotherapy as second-line treatment in pretreated EGFR-mutated advanced NSCLC (21,22). Several phase III trials are ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…There are 23 clinical trials and 37 retrospective studies in patients with EGFR -mutant-positive NSCLC based on immunotherapy, and most data of them are from subgroups ( Tables 1 and 2 ) 9 , 11 , 17 74 . When pooling activity data in the meta-analysis indeed, the pooled ORR of EGFR -mutant patients treated with immunotherapy in clinical trials was 6% (95% CI: 3–9, I ² = 0%), while 8% (95% CI: 6–11, I ² = 43%) in retrospective studies ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has also investigated the efficiency of combinations of immunotherapy and chemotherapy. The ORR of toripalimab combined with carboplatin/pemetrexed in an intention-to-treat population was 54.8% ( Zhang et al, 2019 ), and that of tislelizumab combined with albumin paclitaxel/carboplatin was 59.4% ( Han et al, 2021 ). Immunotherapy combined with chemotherapy showed an advantage in terms of ORR in EGFR-mutant patients, but the final data remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%